NON-PARAMETRIC MANN-KENDALL AND SEN’S SLOPE ESTIMATE AS A METHOD FOR DETECTING TREND WITHIN HYDRO-METEOROLOGICAL TIME SERIES: A REVIEW - Nura Idris Abdullahi; Shamsudden Mohammed; Yusuf Owoseni; Stephen Ijimdiya; Khalid Suleiman (Academy Journal of Science and Engineering)
Climate and water resources are interconnected in a complex way such that a change in any one induces a change in another. Trend analysis is usually employed while assessing the long-term impact of climate variability on the environment, particularly water resources. Parametric and non-parametric statistical methods were employed at various times for trend tests depending on the nature of the data at hand. Non-parametric procedures for detecting trends were found to be suitable for hydro-meteorological time series. This paper, therefore, reviewed some non-parametric trend tests of hydro-meteorological time series and their application and found Mann-Kendall and Sen’s Slope Estimate method as a suitable method of assessing trends within hydro-meteorological time series.